Comparative epigenomics in distantly related teleost species identifies conserved cis-regulatory nodes active during the vertebrate phylotypic period - Tena, Juan J.; Wittbrodt, Joachim (Genome research, 2014)
An international, peer-reviewed genome sciences journal featuring outstanding original research that offers novel insights into the biology of all organisms
Gesehen am 08.02.2017